The Possibility of Practical Thought in Marion based on Cartesian Esteem - Murga, Ezequiel D. (2024)
According to Jean-Luc Marion, the subject is responsible for the phenomenalization of the given. This process—characterized as “hermeneutic” by the author—implies a discrimination concerning which is the most adequate way to show the phenomenon. For this to be possible, however, a modality of thought which does not deal with objects but with events is needed. This paper argues that this modality—suitable for deciding the way of phenomenalization of the given—can be found in practical thought. Firstly, I trace back this possibility to the Cartesian esteem. Secondly, I discuss it with reference to the Aristotelian prudence. Finally, I relate both approaches to comprehension (Verstehen), a concept that Marion picks up from Heidegger and Gadamer.